A catenane host system containing integrated triazole C-H hydrogen bond donors for anion recognition. - White, N; Beer, P (2012)
A 3,5-bis(triazole)-pyridinium motif is integrated into a catenane structural framework via chloride anion templation. The catenane host system displays a high degree of selectivity for halide anions over dihydrogen phosphate.